النمذجة التحليلة من أجل تحليل الدقة لنظام قياس الزاوية (Latakia University Journal -Engineering Sciences Series, 2019)
A two-sensor system based on the AMR effect is often used in automotive applications to compute the absolute angle of a steering-wheel. However, many possible errors may come from the sensors or from the signal conditioning electronics caused by the measurement errors or the input noise. These errors affect on the precision of the system. Thus, this demands on the precision analysis to determine whether the system delivers an accurate or correct output in the presence of the errors. In this research, angular deviations caused by errors or noise will be modeled for the two sensor- system based on AMR sensors. Furthermore, the effect of the deviation on the precision of the system will be analyzed. MATLAB program is adopted for modeling, simulation, and evaluation of our results. يستخدم نظام ثنائي الحساس الذي يعتمد على تأثير AMR في كثير من التطبيقات الخاصة بالسيارات لحساب الزاوية المطلقة a لدولاب القيادة. لكن العديد من الأخطاء الممكنة الحدوث في الحساسات أو في الكترونيات مكيفات الاشارة سببها أخطاء القياس أو ضجيج على دخل النظام. تؤثر هذه الاخطاء على دقة نظام القياس. لذلك لابد من تحليل الدقة لتحديد فيما اذا كان النظام سيعطي خرجاً دقيقاً أو صحيحاً بوجود هذه الأخطاء. في هذا البحث سيتم نمذجة الانحرافات في الزاوية المطلقة a الناتجة عن الأخطاء أوالضجيج لنظام ثنائي الحساس الذي يعتمد على تأثير AMR. علاوة على ذلك سيتم تحليل تأثير الانحرافات على دقة النظام. يستخدم برنامج ال MATLAB من أجل نمذجة ومحاكاة وتقييم النتائج التي تمّ الحصول عليها.